Nindai Dalam Tradisi Perkawinan Adat lampung: Nindai Dalam Tradisi Perkawinan Adat lampung - Zainudin Hasan; Navaro Dzaky (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The nindai tradition is an important stage in the traditional Lampung wedding ceremony, reflecting values of prudence, politeness, and respect for socio-cultural order. Nindai is performed by the prospective groom's family as a form of exploration of the prospective bride, with the aim of assessing their background, character, and harmony between the two families. This study aims to understand the philosophical meaning, social function, and relevance of the nindai tradition in contemporary Lampung society. The method used in this study is a descriptive qualitative approach, utilizing literature sources, interviews with traditional leaders, and observations of traditional Lampung wedding ceremonies. The results indicate that the nindai tradition serves not only as a partner selection process but also as a means of strengthening social ties between families and maintaining honor (piil pesenggiri) in the Lampung community. Although the influence of modernization has caused this tradition to become less common, the values embodied in nindai remain relevant and can serve as moral guidelines for building a harmonious and dignified family.